Utopisk slægtskab i udryddelsens tid - Andersen, Iben Engelhardt (K&K - Kultur og Klasse, 2020)
This article examines how utopian and ecological thinking connect in light of the ongoing eco-catastrophe. While the dystopic genre might be timely as it depicts an affective landscape of fear and hopelessness and communicates ideas about how things can get much worse, the article suggests that utopian imagination is necessary but only possible if it connects with an existing ecology. It presents three utopian perspectives on the entanglements of reproduction and ecological sustainability –Inger Christensen’s circular energy, Donna Haraway’s non-reproduction, and Hiromi Ito’s radical kinship – that link utopian imagination, feminist temporalities and questions of sustainability. The focus on birth, childhood and kinship illustrates how biology, social practices and phantasms affect one another and how ecology brings these levels together, while connecting intimate questions and global problematics. The analyzed texts articulate instances of “utopian kinship” that sidestep the mechanisms of reproductive futurism or reproduction understood as a confirmation and continuation of the way things are. As such, they point to the reproductive sphere as a place for resistance: queer growth, multispecies kinship, nature’s work against capitalism’s principles of development.